Thermostable glucose-tolerant glucoamylase produced by the thermophilic fungus Scytalidium thermophilum - Aquino, A.C.M.M; Jorge, J.A; Terenzi, H.F; Polizeli, M.L.T.M. (Universidade de Sao Paulo (Brazil). Departamento de Biologia) (Folia microbiologica, 2001)
Glucoamylase produced by Scytalidium thermophilum was purified 80-fold by DEAE-cellulose, ultrafiltration and CM-cellulose chromatography. The enzyme is a glycoprotein containing 9.8 % saccharide, pI of 8.3 and molar mass of 75 kDa (SDS-PAGE) or 60 kDa (Sepharose 6B). Optima of pH and temperature with starch or maltose as substrates were 5.5/70 deg C and 5.5/65 deg C, respectively. The enzyme was stable for 1 h at 55 deg C and for about 8 d at 4 deg C, either at pH 7 or pH 5.5. Starch, amylopectin, glycogen, amylose and maltose were the substrates preferentially hydrolyzed. The activity was activated by 1 mmol/L Mg**2+ (27 %), Zn**2+ (21 %), Ba**2+ (8 %), Mn**2+ (5 %). Km and vlim values for starch and maltose were 0.21 g/L, 62 U/mg protein and 3.9 g/L, 9.0 U/mg protein, respectively. Glucoamylase activity was only slightly inhibited by glucose up to a 1 mol/L concentration.